Genome Sequencing of Streptomyces olivaceus SCSIO T05 and Activated Production of Lobophorin CR4 via Metabolic Engineering and Genome Mining - Chunyan Zhang; Wenjuan Ding; Xiangjing Qin; Jianhua Ju (Marine Drugs, 2019)
Marine-sourced actinomycete genus Streptomyces continues to be an important source of new natural products. Here we report the complete genome sequence of deep-sea-derived Streptomyces olivaceus SCSIO T05, harboring 37 putative biosynthetic gene clusters (BGCs). A cryptic BGC for type I polyketides was activated by metabolic engineering methods, enabling the discovery of a known compound, lobophorin CR4 (1). Genome mining yielded a putative lobophorin BGC (lbp) that missed the functional FAD-dependent oxidoreductase to generate the d-kijanose, leading to the production of lobophorin CR4 without the attachment of d-kijanose to C17-OH. Using the gene-disruption method, we confirmed that the lbp BGC accounts for lobophorin biosynthesis. We conclude that metabolic engineering and genome mining provide an effective approach to activate cryptic BGCs.